Maximally regular net for the rotational ellipsoid - POHÁNKA, Vladimír (Contributions to Geophysics and Geodesy, 2021)
The maximally regular net on the unit sphere is adapted for the surface of the rotational ellipsoid. The mapping between these two surfaces is performed by using the ellipsoidal coordinates. The values of coordinates of vertices of the net at the surface of the Earth reference ellipsoid WGS 84 were calculated from the coordinates of vertices at the unit sphere.